Non Paramectric Stability Analysis for Yield of Hybrid Chili Pepper (Capsicum annuum L.) Across Six Different Environments - Syukur, Muhamad; Sujiprihati, Sriani; Yunianti, Rahmi; Kusumah, Darmawan Asta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTThe objectives of this study were to evaluate several chili pepper hybrids whith high yielding character and stable at six environments based on some non-parametric stability analyses, and to study the correlation among the stability of non-parametric methods. The hybrid of chili pepper (7 candidates varieties and 5 commercial hybrid cultivars) were grown in a randomized complete block design with 3 replications in 6 different environments. Ten nonparametric stability methods were used to identify the stable genotypes.  According to the SI(3), RS, NPi(1), NPi(2), NPi(3) and NPi(4) stability parameters, Imperial was the most stable hybrid. According to the SI(1), SI(2) and TOP  stability parameters and yield, IPB CH3 was the most stable hybrid.  In this study, the high TOP values were associated with the yield. Nonetheless, the results of the other non parametric (SI(6), NPi(3) and NPi(4)) were negatively correlated to the yield. The results also revealed that based on the non parametric stability test, the results could be classified into 2 groups, according to the agronomic and biological stabilities. Keywords: chili pepper, environment, non-parametric stability, yield